AI and ML-Driven Immersive Technologies: A New Era in Education - Biswajit Gayen; Sattik Mondal; Arna Bhaumik; Snehasri Mondal; Chittaranjan Mondal; Raghunath Maji; Saikat Majumder (International Journal of Education Sciences, 2026)
The very fast adoption of Artificial Intelligence (AI) and Machine Learning (ML) in education has transformed contemporary teaching and learning ecosystems driven by advances in immersive technologies and the growing engagement of global technology leaders with virtual environments. AI-powered educational platforms enable adaptive and personalized learning pathways by dynamically adjusting content, pace and instructional strategies to learners’ preferences, abilities and learning styles by improving engagement, retention and academic outcomes. Deep learning models and predictive analytics are further reshaping pedagogical practices by supporting data-driven decision making, early identification of learning difficulties, and targeted interventions while simultaneously raising critical concerns related to ethics, data privacy, equity and long-term sustainability.Immersive technologies such as Extended Reality (XR), blockchain and edge computing are expanding the scope of interactive, collaborative and simulation-based learning. These technologies facilitate experiential learning, virtual laboratories and global collaboration, while promoting more inclusive and equitable access to quality education across geographical and socioeconomic boundaries. Augmented Reality (AR) and Mixed Reality (MR) enhance instructional delivery by bridging physical and digital learning spaces whereas AI-driven analytics provide educators with actionable insights to monitor progress, personalize instruction and reduce achievement gaps.This article emphasizes the evolving role of AI and ML in education by incorporating recent developments, applications, benefits and challenges. It also emphasizes the potential of intelligent and immersive systems to redefine educational models while underscoring the need for responsible, ethical and sustainable integration to ensure inclusive and effective learning environments for the future across diverse disciplines, institutions, cultures and lifelong learning contexts worldwide.
Keywords: Adaptive Learning Systems; Educational Data Analytics; Immersive Technologies; Machine Learning; artificial intelligence